Emotional and Psychological Well-Being, Emotion Regulation, and Intent Attribution of Children Whose Earthquake Bereaved - Erol, Mustafa; Temur, Murat; Erol, Ahmet; Dayan, Gokhan (SAGE PUBLICATIONS INC, 2025)
This study compares the emotion regulation, intent attribution, and emotional and psychological well-being (PWB) of children who lost their loved ones in the earthquakes that occurred in T & uuml;rkiye on February 6, 2023, with children who were not directly affected by the earthquakes and who were nonbereaved. The participants consisted of 216 children living in earthquake zones who were bereaved and 202 children who were not living in earthquake zones and were nonbereaved. As a result of the study, it was found that the PWB and emotion regulation of children who were nonbereaved were statistically significantly higher than those of children who were bereaved. No significant difference was found between bereaved and nonbereaved children in terms of intent attribution. In addition, it was determined that significant positive relationships existed between PWB and emotion regulation in children who were nonbereaved. These relationships were seen at a lower level in children who were bereaved.
Keywords: earthquake; bereavement; psychological well-being; intent attribution; emotion regulation; POSTTRAUMATIC-STRESS-DISORDER; AGGRESSIVE-BEHAVIOR; ANGER; ASSOCIATIONS; EXPRESSION; DEPRESSION; DISASTER; MOTHERS; Psychology; Biomedical Social Sciences